Noninvasive imaging of thermal fields induced in soft tissues in vitro by pulsed focused ultrasound using analysis of echoes displacement - KARWAT, Piotr; LITNIEWSKI, Jerzy; KUJAWSKA, Tamara; SECOMSKI, Wojciech; KRAWCZYK, Kazimierz (Archives of Acoustics, 2014)
Therapeutic and surgical applications of focused ultrasound require monitoring of local temperature rises induced inside tissues. From an economic and practical point of view ultrasonic imaging techniques seem to be the best for a temperature control. In this work an attempt to apply the method of the ultrasonic echoes displacement estimation for monitoring of local temperature rise in tissue during its heating by focused ultrasound is presented. The estimated temperature rise was compared to the data measured with thermocouple. The obtained results enable to evaluate the temperature fields induced in tissues by pulsed focused ultrasonic beams using non-invasive imaging ultrasound technique.